Genealogy Story dalam Cerita Bidadari dari Indonesia Timur: (Toumatenden, Tomaseseq Ditingalor, Puteri Bungso, dan Punteri Pinto) - Sunarti, Sastri; Tjayandari, Lily; Wagiu, Meily Meiny; Syahrul, Ninawati; Lewier, Mariana (Kamaya: Jurnal Ilmu Agama, 2025)
Indonesia, with its diverse cultural heritage and rich history, has various mythologies and folktales featuring supernatural beings, including angels or celestial beings that come down to earth. The story of Angels who came down to earth found in various region in Indonesia, such as the story of Toumatenden (North Sulawesi), Tomaseseq Ditingalor (West Sulawesi), Putri Bungso (Ambon Island), and Punteri Pinto (Pantar Island). Apart from these four areas, the theme of angels descending to earth are also found in many regions of Indonesia, from Aceh to Papua. This research tries to explore the four angel stories from four regions in Eastern Indonesia. These four stories have a genealogy of ancestral origins that interwoven with the genealogy of ancestors of Minahasa, Mandar, Tehupelasurry, and Helang Dohi tribes in Pantar NTT. This Study uses descriptive qualitative method which requires field research. The result of this study has found that angel stories not only talk about angelic beings but also used as a tool to legitimize the identity and genealogy of ancestors who have special features. It shows a connection with the belief system in the celestial ‘samawi’ religion. The stories are also transformation from the story of ‘Adam and Eve’, the first humans or ancestors.